2017
DOI: 10.1007/978-94-024-1134-8_10
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Electrified Dust and Dust Devil Electrodynamics to Martian Atmospheric Electricity

Abstract: Atmospheric transport and suspension of dust frequently brings electrification, which may be substantial. Electric fields of 10 kV m −1 to 100 kV m −1 have been observed at the surface beneath suspended dust in the terrestrial atmosphere, and some electrification has been observed to persist in dust at levels to 5 km, as well as in volcanic plumes. The interaction between individual particles which causes the electrification is incompletely understood, and multiple processes are thought to be acting. A variati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(38 citation statements)
references
References 156 publications
1
37
0
Order By: Relevance
“…A paradoxical example of these interactions is the Martian atmosphere, where electricity phenomena is expected to be important 11 . The persistent layer of dust that covers the surface expanse of Mars can be easily lifted and dispersed by local weather phenomena such as dust devils and regional storms 12 . The dust particles accumulate in clouds that can morph into global storms known to encircle the entire planet for as long two Earth years 13 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A paradoxical example of these interactions is the Martian atmosphere, where electricity phenomena is expected to be important 11 . The persistent layer of dust that covers the surface expanse of Mars can be easily lifted and dispersed by local weather phenomena such as dust devils and regional storms 12 . The dust particles accumulate in clouds that can morph into global storms known to encircle the entire planet for as long two Earth years 13 .…”
Section: Introductionmentioning
confidence: 99%
“…To compound this extreme weather, the prevailing low pressures of order 10 mbar in the CO 2 -rich Martian atmosphere may favor electric discharges because of the resulting much lower values of the breakdown electric field, which is of order 5–25 kV m −1 , as opposed to the 3 MV m −1 observed on Earth at sea level 14 – 16 . As a result, the dust clouds are thought to be an excellent brewing environment for electric discharges that might pose risks to Mars surface exploration instruments and crews 12 , 15 – 17 . In contrast to other planets in the Solar System, however, conclusive measurements of atmospheric electricity phenomena in Mars are lacking 18 , more so after the recent crash of ESA’s Schiaparelli Mars lander in 2016 that carried onboard a dust analyzer to elucidate some of these unknowns.…”
Section: Introductionmentioning
confidence: 99%
“…Following Michaels (2006), Barth et al (2014) coupled a detailed aerosol model (operating on discrete mass bins) to the LES model of Rafkin et al (2001) run at an improved horizontal resolution of 33 m, and incorporated dynamic spatial redistribution of initially charged dust particles in order to evaluate the possibilities for electric fields generated within the dust devils in their LES. Using the Microscopic Triboelectric Simulation (MTS; see Harrison et al (2016) in this issue for further description), they added tracers to represent the moments of a distribution of particle charges across each mass bin. As the dust was lifted and redistributed spatially by both convective vortices and gravitational settling, the charge density at each grid point would also evolve.…”
Section: Perspectives and Challengesmentioning
confidence: 99%
“…The famous Miller and Urey experiment of the 1950s found that electrical discharges generated in conditions mimicking the early Earth's atmosphere produced amino acids, the starting point for life (Parker et al ., ). More recent work has shown that energetic electrons accelerated in the electric fields in Martian dust storms can affect atmospheric chemistry, which may also be relevant for life (Harrison et al ., ). The possibility of life elsewhere in the universe, and the conditions needed for it, remains one of the biggest scientific questions facing mankind and provides a major motivation.…”
Section: Introductionmentioning
confidence: 97%